Special cases of martensite compatibility: A near single-variant habit-plane and the martensite of nanocrystalline NiTi - Petersmann Manuel; Antretter Thomas; Waitz Thomas (MATEC Web of Conferences, 2015)
Lattice parameters measured near the high temperature (~1000°C) bcc α to hcp β transformation in an intermetallic Mo-containing γ-TiAl based alloy indicate a middle valued eigenvalue of the corresponding deformation gradient near 1. Habit-planes calculated under the assumption of a simple slip as lattice invariant shear, agree with experimentally determined orientations of the lens like plates recorded via electron backscattering. By contrast, twinning as invariant lattice shear has been investigated in nanocrystalline NiTi. Here the grain size causes the formation mechanism of the martensite to change from a “herring-bone” morphology faciliting a habit-plane between two twinned laminates and the austenite to a single laminate, which in the nonlinear theory formally cannot form a habit-plane with the austenite. Since this might cause high accommodation strains, the effectiveness of stress accommodation of martensite formed in neighboring grains of a polycrystal is investigated. Subsequent numerical microstructural modeling is outlined. The resulting energetically most favorable transformation sequence yields the transformation kinetics.